Therapeutic potential of histamine H4 receptor agonists in triple‐negative human breast cancer experimental model. (15th August 2013) - Martinel Lamas, Diego J; Croci, Maximo; Carabajal, Eliana; Crescenti, Ernesto J V; Sambuco, Lorena; Massari, Noelia A; Bergoc, Rosa M; Rivera, Elena S; Medina, Vanina A
<x xml:space="preserve">Abstract</x> Background and Purpose The presence of the histamine H4 receptor (H4R) was previously reported in benign and malignant lesions and cell lines derived from the human mammary gland. The aim of this work was to evaluate the effects of H4R ligands on the survival, tumour growth rate and metastatic capacity of breast cancer in an experimental model. Experimental Approach Xenograft tumours of the highly invasive human breast cancer cell line MDA‐MB‐231 were established in immune deficient nude mice. The following H4R agonists were employed: histamine (5 mg kg−1), clozapine (1 mg kg−1) and the experimental compound JNJ28610244 (10 mg kg−1). Results Data indicate that developed tumours were highly undifferentiated, expressed H4R and exhibited high levels of histamine content and proliferation marker (PCNA) while displaying low apoptosis. Mice of the untreated group displayed a median survival of 60 days and a tumour doubling time of 7.4 ± 0.6 days. A significant decrease in tumour growth evidenced by an augment of the tumour doubling time was observed in the H4R agonist groups (13.1 ± 1.2, P < 0.01 in histamine group; 15.1 ± 1.1, P < 0.001 in clozapine group; 10.8 ± 0.7, P < 0.01 in JNJ28610244 group). This effect was associated with a decrease in the PCNA expression levels, and also reduced intratumoural vessels in histamine and clozapine treated mice. Histamine significantly increased median survival (78 days; Log rank Mantel‐Cox Test, P = 0.0025; Gehan‐Breslow‐Wilcoxon Test, P = 0.0158) and tumoural apoptosis. Conclusions and Implications Histamine through the H4R exhibits a crucial role in tumour progression. Therefore, H4R ligands offer a novel therapeutic potential as adjuvants for breast cancer treatment. Linked Articles This article is part of a themed issue on Histamine Pharmacology Update. To view the other articles in this issue visit http://dx.doi.org/10.1111/bph.2013.170.issue‐1